Preparation of core–shell magnetic ion-imprinted polymer for selective extraction of Pb(II) from environmental samples - Zhang, Minglei; Zhang, Zhaohui; Liu, Yunan; Yang, Xiao; Luo, Lijuan; Chen, Jutao; Yao, Shouzhuo (Chemical engineering journal (Lausanne, Switzerland : 1996), 2011)
► Solid phase extraction combined with magnetic ion-imprinted sorbents was used for selective extraction of Pb(II). ► A core–shell magnetic imprinted polymer based on magnetic Fe 3O 4 was synthesized. ► 3-(2-Aminoethylamino)propyltrimethoxysilane was employed as functional monomers in the preparation process of Pb(II) ion-imprinted polymer. A novel magnetic ion-imprinted polymer (Fe 3O 4@SiO 2@IIP) was synthesized by using 3-(2-aminoethylamino)propyltrimethoxysilane (AAPTS) as the functional monomer, tetraethylorthosilicate (TEOS) as the cross-linker and Pb(II) as the template and evaluated for selective extraction of Pb(II) from environmental sample by magnetic solid phase extraction (M-SPE) procedure. The factors affecting separation and preconcentration of the target heavy metals involving pH, eluting solvent and sample volume were studied in detail. Under the optimized experimental conditions, the kinetics adsorption and adsorption capacity of the Fe 3O 4@SiO 2@IIP toward Pb(II) were estimated. The results indicated that the adsorption mechanism is corresponding with the second-order adsorption process with correlation coefficient ( r 2 = 0.990), and the maximum adsorption capacity is 19.61 mg g −1. The relative selectivity factor ( β) values of Pb(II)/Cu(II), Pb(II)/Zn(II), Pb(II)/Cd(II) and Pb(II)/Hg(II) are 7.41, 6.76, 3.75 and 6.39, respectively. The Fe 3O 4@SiO 2@IIP was applied for extracting and detecting of Pb(II) in real environmental samples combined with atomic adsorption spectrometer successfully with high recoveries of 98.0%.